Searching of the Larvian Identity Within Contemporary Design and Design Education - Strode, Aina; Apele, Diāna (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2012)
Signs as symbols give the knowledge about universe. Latvian identity is an important theme of design in nowadays. The tendency which is related with Latvian is to return to the ancient wisdom and ancient crafts’ skills. The aim of the study: to explore the usage of ethnographic motif, conceptions of stylization and transformation within professional design and design studies. The methods of research: theoretical - analysis of the literature; empirical - qualitative research methods such as the analysis of the study tasks implemented by the RA study program "Interior Design", observation and analysis of students' creative activity. Research base: Rezekne Higher Education and Design Faculty of professional bachelor's study program "Interior Design".